STRATEGI LEMBAGA DAKWAH DALAM INOVASI KEWIRAUSAHAAN DI ERA DISRUPTIF - Syahrizal, Syahrizal; Castrawijaya, Cecep (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2025)
The disruptive era will add to increasingly open global competition, many challenges faced by today's society. Each country must compete by highlighting the superiority of its respective resources, which is called entrepreneurship. Considering the importance of entrepreneurship, an entrepreneurial spirit needs to be instilled as early as possible. At the same time, in entrepreneurial outcomes, something called innovation is needed which has an important role in developing a number of new ideas, before being transformed into a product, the previous innovation must be evaluated to study whether the product will be successful on the market. Therefore, an institution needs to have the right strategy in marketing. Likewise with missionary institutions, in order to encourage goodness and prevent evil, there needs to be a strategy for innovation in the field of entrepreneurship. When an institution only focuses on traditional methods and does not look at modern things, the da'wah institution will position itself as an institution that only includes a vision and mission without any changes. Especially in this disruptive era, da'wah institutions are required to be part of immediately adapting to various advances in technology and knowledge. The research results show that da'wah institutions must have an innovation strategy in preaching, namely developing entrepreneurship programs, technological innovation in preaching, where da'wah institutions are not blind to the existence of technology that offers efficiency in the entrepreneurial development process in a disruptive era, collaboration that creates cooperation with various parties who have the same ideology and vision, and creates new business models.Keywords: Da'wah Institutions, Entrepreneurship, Innovation, Disruptive Era[Era disruptif akan menambah persaingan global yang semakin terbuka, banyak tantangan yang dihadapi oleh Masyarakat sekarang ini. Setiap negara yang harus bersaing dengan menonjolkan keunggulan sumberdaya masing-masing yang disebut dengan wirausaha. Mengingat pentingnya kewirausahaan maka jiwa wirausaha perlu ditanamkan sedini mungkin. Tatkala dengan itu, dalam hasul wirausaha maka diperlukan yang Namanya inovasi yang memiliki peran penting dalam mengembangkan sejumlah ide-ide baru, sebelum ditransformasikan menjadi produk, inovasi sebelumnya harus dievaluasi untuk dikaji apakah produk tersebut akan berhasil dipasarkan. Maka dari itu sebuah lembaga perlu mempunyai strategi yang tepat dalam pemasaran. Begitu pula dengan lembaga dakwah, dalam mengajak kebaikan danm mencegah kemungkaran perlu adanya strategi dalam melakukan inovasi dalam bidang wirausaha. Tatkala lembaga hanya berfokus pada cara tradisional dan tidak melirik pada hal modern, maka lembaga dakwah tersebut akan meletakkan posisinya sebagai lembaga yang hanya mencantumkan visi misi tanpa adanya perubahan. Terutama pada era disruptif, lembaga dakwah dituntut untuk menjadi bagian yang segera beradaptasi dengan berbagai kemajuan teknologi dan pengetahuan. Hasil penelitian menunjukkan bahwa lembaga dakwah harus memiliki strategi inovasi dalam berdakwah yaitu pengembangan program kewirausahaan, inovasi teknologi dalam dakwah, Dimana lembaga dakwah tidak buta terhadap adanya teknologi yang memberikan tawaran efisiensi dalam proses perkembangan kewirausahaan di era disruptif, kolaborasi yang menciptakan Kerjasama dengan berbagai pihak yang mempunyai ideologi dan visi yang sama, dan menciptakan model bisnis baru]. Kata Kunci: Lembaga Dakwah, Kewirausahaan, Inovasi, Era Disruptif